Chlorophyll fluorescence imaging analysis of the responses of Antarctic bottom-ice algae to light and salinity during melting - Ryan, KG; Tay, ML; Martin, AR; McMinn, A; Davy, SK (Journal of Experimental Marine Biology and Ecology, 2011)
Bottom-ice algae within Antarctic sea ice were examined using chlorophyll fluorescence imaging. The detailedstructure of the bottom-ice algal community growing in the platelet and congelation layers of solid pieces ofsea ice was evident for the first time in chlorophyll imaging mode. Strands of fluorescence representing algalcells were clearly visible growing upward into brine channels in a fine network. Images of effective quantumyield (PSII) revealed that thePSII of algae embedded in the sea ice was approximately 0.5. Furthermore,PSIIdecreased slightly with distance from the icewater interface.The response of Antarctic sea ice algae to changes in irradiance and salinity, and the effects of slowly warmingand melting the ice block sample were examined using this system. The PSII of bottom-ice algae decreased asirradiance increased and salinities decreased. Bottom-ice algae appear to be most vulnerable to changes intheir environment during the melting process of the ice, and this suggests that algae from this region of the icemay not be able to cope with the stress of melting during summer.Chlorophyll fluorescence imaging provides unprecedented imagery of chlorophyll distribution in sea ice andallows measurement of the responses of sea ice algae to environmental stresses with minimal disruption totheir physical habitat. The results obtained with this method are comparable to those obtained with algae thathave been melted into liquid culture and this indicates that previous melting protocols reveal meaningfuldata. In this chlorophyll imaging study, rapid light curves did not saturate and this may prevent further use ofthis configuration.